Neuroprotection of Gastrodia elata polyphenols against H2O2-induced PC12 cell cytotoxicity by reducing oxidative stress - Tan, Weijian; Zheng, Qinhua; Feng, Kexin; Feng, Xiaolin; Zhong, Wenting; Liao, Caiyu; Li, Shangjian; Liu, Yuntong; Hu, Wenzhong (Frontiers in Pharmacology, 2022)
It has been suggested that oxidative stress (OS) has a role in the development of aging and neurodegenerative disorders. Biological molecules are easily damaged by reactive oxygen species, which can ultimately result in necrotic or apoptotic cell death. Foods containing phytochemicals, such as phenolic compounds, may have potential preventive effects against several diseases, including alzheimer’s disease (AD), according to epidemiological and in vitro research. Gastrodia elata is a well-known homology of medicine and food plant that has been used for centuries in China and other East Asian countries to treat central nervous system disorders. In this study, we focused on the potential of the extract, Gastrodia elata polyphenols (GPP), for the prevention and treatment of AD. H2O2 induced PC12 cell damage was used to simulate the oxidative stress of AD. The effects of GPP on the injury model were evaluated by cell survival rate, lactate dehydrogenase (LDH), lipid peroxidation (MDA), production of intracellular antioxidant enzymes, reactive oxygen species (ROS), mitochondrial membrane potential (MMP), cellular inflammation level and apoptosis level. The results showed that GPP pretreatment had a protective effect by increasing cell viability, reducing lactate dehydrogenase infiltration, decreasing MDA and increasing intracellular antioxidant enzymes, diminishing reactive oxygen species production and decreasing mitochondrial membrane potential, reducing cell inflammation and decreasing apoptosis. Accordingly, it is suggested that GPP possessed promising neuroprotective benefits which enabled the prevention or therapeutic implementation of AD along with serving as a reference towards the exploitation of functional foods or drugs derived from Gastrodia elata.